Differences in Effectiveness of Clogs and Captive Path Games to Improve Gross Motor Skills in Children 4-5 Years - Setiawaty, Ruth Eka Mudji; Darminto, Eko; Jannah, Miftakhul (International Journal for Educational and Vocational Studies, 2020)
This study aims to determine (1) Effective Clogs game to improve gross motor skills of children aged 4-5 years. (2) Captive Path game is effective in increasing the gross motor skills of children aged 4-5 years (3) There is a difference in the effectiveness of the game of Clogs and Captive Path increases the gross motor abilities of children aged 4-5 years. This research uses a quantitative research design. The analysis of the results of the study was carried out using the parametric statistical approach, which required a normality test, a homogeneity test, and to determine differences in the hypothesis, a T-test was performed on the N-gain score. The results showed that: (1) based on the normality test, the values for pre-test and post-test were greater than 0.05, so the clogs had normal distribution data. Homogeneity test results in pre-test and post-test values greater than 0.05, so clogs have homogeneous data. (2) based on the normality test, the values for the pre-test and post-test are greater than 0.05, then the captive path game has normally distributed data. (3) Based on the T-test on the N-gain Score, the sig value < 0.05 for clogs games concluded that clogs games effectively improve the gross motor skills of children aged 4-5 years while for captive path game produces sig values > 0.05 concluded that the game of captivity ineffective in increasing gross motor skills of children aged 4-5 years.